Enhancing Ecopreneurship Competency Through Bidan Elok E-Learning Based on Local Wisdom - Haris, Risma; Duygulu, Sergul; Hafidah, Andi; Syakur, Rosdiana; Djatmiko, Budi; Maryam, Andi; Indrawati, Andi (Pandawan, 2025)
Local wisdom-based ecopreneurship focuses on sustainability and environmental preservation, offering midwives the opportunity to utilize local natural resources efficiently while preserving social and cultural values. In South Sulawesi, integrating ecopreneurship into midwifery education remains underexplored. This study evaluates the effectiveness of the